Propagation of Sedum adolphii In vitro - Alani, N. K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Sedum adolphii stem cutting 1-2 cm were sterilized and cultured on different media . The favorable medium for callus formation was Murashige and skoog (MS, 1962)supplemented with Banzylaminopurine ( BAP) plus Naphalene acetic acid (NAA) in106M each . Whereas, the best medium for differentiation was MS ,1962 supplemented with BAP 10-7M and NAA10-7M . The formed shoots were transferred to media without Auxin (control) or with different (NAA) concentrations (10-6and 10-7M) . The best rooted shoots were on control, transferred successfully to jeffy 7 discs and to the green house after 3 weeks.